Genetic counseling for patients and families with hereditary breast and ovarian cancer in a developing Asian country: An observational descriptive study - Yoon, Sook Yee; Thong, Meow Keong; Mohd Taib, Nur Aishah; Yip, Cheng Har; Teo, Soo Hwang (Springer, 2011)
Genetic counseling (GC) and genetic testing are vital risk management strategies in hereditary breast and ovarian cancer (HBOC) syndromes. Hitherto, cancer genetic testing amongst Asians has been described only in developed and high-income Asian countries. We studied the uptake and acceptance of GC and genetic testing services to Asian BRCA carriers in a middle-income country. A total of 363 patients were tested by full sequencing and large rearrangement analysis of both BRCA1 and BRCA2 genes in the Malaysian Breast Cancer (MyBrCa) Genetic Study. Of these, 49 index patients (13.5%) were found to carry deleterious mutations. GC pre- and post- result disclosures were provided and these groups of patients and their families were studied. GC and genetic testing were accepted by 82% of Malaysian patients at high risk for HBOC syndromes. However, risk assessment was limited by large, geographically dispersed, often polygamous or polyandrous families, and the lack of complete cancer registry. Cultural taboos about cancer diagnoses, social marginalization and lack of regulatory control of genetic discrimination were significant concerns. Only 78% of index patients informed their families of their risks and 11% of relatives came forward when offered free counseling and testing. Even when GC and genetic testing are provided at no cost, there remain significant societal and regulatory barriers to effective cancer genetic services in this underserved Asian population. Families believe there is a need for regulatory protection against genetic discrimination. Further studies are needed in the area of increasing awareness about the potential benefits of GC and genetic testing in Asians. © 2011 Springer Science+Business Media B.V.